Bevacizumab and Weekly Docetaxel in Patients with Metastatic Castrate-Resistant Prostate Cancer Previously Exposed to Docetaxel - Filippo Francini; Alessandra Pascucci; Edoardo Francini; Gianluca Bargagli; Raffaele Conca; Antonella Licchetta; Giandomenico Roviello; Ignazio Martellucci; Giorgio Chiriacò; Salvatora Tindara Miano; Giuseppe Marzocca; Antonio Manganelli; et al. (Prostate Cancer)
Background. The aim of this paper was to evaluate the activity and tolerability of docetaxel (D) and bevacizumab (Bev) in patients with metastatic castrate-resistant prostate cancer (CRPC) previously exposed to D. Methods. Treatment consisted of D 30 mg/m2 i.v. for four consecutive weekly administrations followed by a 2-week rest interval, in addition to Bev 5 mg/kg i.v. every 2 weeks. Results. Forty-three patients were enrolled: a PSA response was observed in 27 patients (62.7%, 95% CI: 0.41 to 0.91), and a palliative response was achieved in 31 patients (72.1%, 95%CI: 0.48 to 1.02). After a median followup of 11.3 months, only five patients had died. The regimen was generally well tolerated. Conclusion. Weekly D + biweekly Bev seems to be an effective and well-tolerated treatment option for patients with metastatic CRPC previously exposed to D-based chemotherapy.